The Influence of Motivation, Compensation, and Physical Work Environment on The Performance of Kumun Health Employees - Fitrina Afrianti (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
This study aims to examine the motivation, compensation, and physical work environment on the performance of the employees of the Kumun Health Center in Sungai Penuh City, a total of 43 respondents. Collecting data in this study's primary data was collected by distributing questionnaires to respondents. This research method uses quantitative methods, while the analysis technique used is multiple linear regression analysis, t-test, f-test, and test the coefficient of determination. Partially, there is an influence between motivation (X1) on employee performance (Y) at the Kumun Health Center in Sungai Penuh City as evidenced by the value of t count ≥ t table(2.874 ≥ 2.02269)with a significant value = 0.007< 0.05. Where is the magnitude of the influence of motivation on the performance of employees of the Kumun Health Center in Sungai Penuh City is 0.072%. There is a positive and significant influence between compensation (X2) partially on employee performance (Y) Kumun Health Center in Sungai Penuh Cityas evidenced by the value of t count ≥ t table (4.484≥ 2.02269) with a significant value = 0.000 <0.05. The compensation amount for the performance of the Kumun Health Center employees in Sungai Penuh City is 32.3%. There is a positive and significant influence between the physical work environment (X3) partially on the performance of employees (Y) at the Kumun Health Center in Sungai Penuh Cityas evidenced by the value of t count ≥ t table (3.228 ≥ 2.02269 ) with a significant value = 0.003 <0.05. The magnitude of the physical work environment on the performance of the Kumun Health Center employees in Sungai Penuh City was 19.3%. There is a simultaneous influence between motivation (X1), compensation (X2), and physical work environment (X3) on employee performance (Y) which is 51.7%. The remaining 48.3% is explained by other causal factors not examined in this study.